2003
DOI: 10.1016/s0042-6822(03)00195-8
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus monkey rhadinovirus (RRV): construction of a RRV-GFP recombinant virus and development of assays to assess viral replication

Abstract: Rhesus monkey rhadinovirus (RRV) is a gamma-2-herpesvirus that is closely related to Kaposi's sarcoma-associated herpesvirus (KSHV/HHV-8). Lack of an efficient culture system to grow high titers of virus, and the lack of an in vivo animal model system, has hampered the study of KSHV replication and pathogenesis. RRV is capable of replicating to high titers on fibroblasts, thus facilitating the construction of recombinant rhadinoviruses. In addition, the ability to experimentally infect naïve rhesus macaques wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 60 publications
1
36
0
Order By: Relevance
“…We previously reported the kinetics of gene expression with regard to immediate-early, early, and late genes during RRV lytic infection and have reported that they are similar to those seen during KSHV reactivation (17,25). We also generated a RRV-green fluorescent protein (GFP) recombinant virus and devised plaque assays and real-time quantitative PCR (QPCR) assays for the determination of virus titers (18). This validates the experimental methods used here.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…We previously reported the kinetics of gene expression with regard to immediate-early, early, and late genes during RRV lytic infection and have reported that they are similar to those seen during KSHV reactivation (17,25). We also generated a RRV-green fluorescent protein (GFP) recombinant virus and devised plaque assays and real-time quantitative PCR (QPCR) assays for the determination of virus titers (18). This validates the experimental methods used here.…”
supporting
confidence: 70%
“…Our lab has previously published the generation of an RRV recombinant virus expressing GFP (RRV-GFP) using homologous recombination (18). We used a similar homologous recombination approach to construct a RRV⌬LANA/GFP recombinant virus by inserting a GFP expression cassette into the R-LANA ORF to disrupt R-LANA transcription and translation.…”
Section: Generation Of a Rrv⌬lana/gfp Recombinant Virusmentioning
confidence: 99%
“…Despite the fact that our bispecific fusion protein ·HN-IL-2 was constructed from the human IL-2 sequence, FACS analysis Several studies (20,25,26) employed real-time PCR to quantify EGFP or GFP transgene expression. To quantify EGFP expression in vivo, we also applied RRT-PCR in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a variety of microbes have been transformed with GFP variants and have shown signifi- cant promise for the study of pathogenesis (70). Thus, the latest generation of GFP reporters allows the investigation of gene expression in individual bacterial cells within specific environments (70)(71)(72)(73)(74).…”
Section: Optical Imagingmentioning
confidence: 99%